DECONSTRUCTING GENDER STEREOTYPES IN DON'T WORRY DARLING (2022): A FEMINIST PERSPECTIVE - Adela Rosa Ariyantie; Syahara Dina Amalia (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2023)
This research aims to analyze key gender stereotypes and how the main character Alice challenging the gender stereotypes portrayed in the film. To analyze the gender stereotypes and how the main character Alice challenges them gender stereotypes. The data were taken from dialogues and scenes containing gender stereotypes that were analyzed by using Deaux’ and Lewis’ (1984) and Brinkman’s and Hamilton’s (2022) theories regarding gender stereotypes. The results show that Alice experienced gender stereotypes in the form of traits, behaviours, physical appearances and occupations, from which the most data are in the traits section and the least in the occupations section. Furthermore, Alice tried to resist the stereotypes by doing many things. Her resistance toward the stereotypes could be identified through these three stages: active, fluid and negotiated. Keywords: challenges, feminist, gender, movie, stereotypes